27. DETERMINATION IN FULL-TERM NEWBORNS WITH SEPSIS AT VIETNAM NATIONAL CHILDREN’S HOSPITAL (2019 - 2021) (Vietnam Journal of Community Medicine, 2023)
Objectives: The study was conducted to determine the role of the diagnosis of neonatal sepsis. Methods: The study was designed using experimental, descriptive research method at the laboratory. Results: Mean values of nCD64, mHLA-DR and SI in full-term newborns with sepsis were 10167.1 ± 6136.9 molecules/cell, 9898.4 ± 14173,9 molecules/cell, and 274.6 ± 287.5, respectively. SI and nCD64 had high values in the diagnosis of sepsis in full-term newborns (AUC = 0.8, p < 0.01), higher than that of CRP, platelets and white blood cells. The sensitivity and specificity of SI at the SI cut-off point > 29.1 were 95.1% and 41.2%, respectively. The sensitivity and specificity of nCD64 at the nCD64 cut-off point > 5004 were 88.2% and 44.5%, respectively. Conclusions: SI and nCD64 are highly valuable in diagnosing sepsis in full-term newborns (AUC = 0.8, p < 0.01).
Keywords: Sepsis, newborns.